Simultaneous enhancement of mechanical and shape memory properties by heat-treatment homogenization of Ti2Ni precipitates in TiNi shape memory alloy fabricated by selective laser melting. (28th February 2022) - Lu, H.Z.; Liu, L.H.; Yang, C.; Luo, X.; Song, C.H.; Wang, Z.; Wang, J.; Su, Y.D.; Ding, Y.F.; Zhang, L.C.; Li, Y.Y.
Highlights: The simultaneous enhancement of mechanical and shape memory properties are obtained by homogenizing Ti2 Ni precipitates in Ti50.6 Ni49.4 SMAs by SLM. The Ti50.6 Ni49.4 SMAs with homogeneous Ti2 Ni precipitates possesses ultimate tensile strength 880 ± 13 MPa and large fracture strain 22.4 ± 0.4%, circumventing the strength-ductility trade-off of TiNi SMAs by additive manufacturing. The Ti50.6 Ni49.4 SMAs with homogeneous Ti2 Ni precipitates also displays 5.32% recoverable strain and above 98% recovery rate, far superior to those in most of TiNi SMAs by additive manufacturing reported so far. Abstract: The excellent shape memory and mechanical properties of TiNi shape memory alloys (SMAs) fabricated using selective laser melting (SLM) are highly desirable for a wide range of critical applications. In this study, we examined the simultaneous enhancement of mechanical and shape memory properties using heat-treatment homogenization of Ti2 Ni precipitates in a Ti50.6 Ni49.4 SMA fabricated using SLM. Specifically, because of the complete solution treatment, nanoscale spherical Ti2 Ni precipitates were homogeneously dispersed throughout the grain interior. Interestingly, the resultant SMA exhibited an ultrahigh tensile strength of 880 ± 13 MPa, a large elongation of 22.4 ± 0.4%, and an excellent shape memory effect, with a recovery rate of > 98% and ultrahigh recoverable strain of 5.32% after ten loading–unloading cycles. These simultaneously enhanced properties are considerably superior than those of most previously reported TiNi SMAs fabricated using additive manufacturing. Fundamentally, the enhancement in tensile strength is ascribed to precipitation strengthening and work hardening, and the large plasticity is mainly attributed to the homogeneous nanoscale globular Ti2 Ni precipitates, which effectively impeded the rapid propagation of microcracks. Furthermore, the enhanced shape memory properties are derived from the suppression of dislocation movement and formation of retained stabilized martensite by the presence of high-density dislocations, nanoscale Ti2 Ni precipitates, and abundant interfaces. The obtained results provide insight into the enhancement of the two types of properties in TiNi SMAs and will accelerate the wider application of SMAs. Graphical abstract: Image, graphical abstract